Development of a participatory Green Infrastructure design, visualization and evaluation system in a cloud supported jupyter notebook computing environment. (January 2019) - Leonard, Lorne; Miles, Brian; Heidari, Bardia; Lin, Laurence; Castronova, Anthony M.; Minsker, Barbara; Lee, Jong; Scaife, Charles; Band, Lawrence E.
Abstract: Land use planners, landscape architects, and water resource managers are using Green Infrastructure (GI) designs in urban environments to promote ecosystem services including mitigation of storm water flooding and water quality degradation. An expanded set of urban sustainability goals also includes increasing carbon sequestration, songbird habitat, reducing urban heat island effects, and improvement of landscape aesthetics. GI is conceptualized to improve water and ecosystem quality by reducing storm water runoff at the source, but when properly designed, may also benefit these expanded goals. With the increasing use of GI in urban contexts, there is an emerging need to facilitate participatory design and scenario evaluation to enable better communication between GI designers and groups impacted by these designs. Major barriers to this type of public participation is the complexity of both parameterizing, operating, visualizing and interpreting results of complex ecohydrological models at various watershed scales that are sufficient to address diverse ecosystem service goals. This paper demonstrates a set of workflows to facilitate rapid and repeatable creation of GI landscape designs which are incorporated into complex models using web applications and services. For this project, we use the RHESSys (Regional Hydro-Ecologic Simulation System) ecohydrologic model to evaluate participatory GI landscape designs generated by stakeholders and decision makers, but note that the workflow could be adapted to a set of other watershed models. Graphical abstract: Image 1 Highlights: Evaluate GI designs with the public and other professions for immediate feedback on GI policies and implementations. RHESSys Jupyter notebooks serve as templates for users to prepare ecohydrologic models. Workflows to facilitate repeatable creation of GI designs into ecohydrologic models. Workflows to engage participation and input from residents and other stakeholders.